1H -NMR Metabolomics Study of the Effect of Cisplatin and Casiopeina IIgly on MDA-MB-231 Breast Tumor Cells - Resendiz-Acevedo, Karen; García-Aguilera, Martha E.; Esturau-Escofet, Nuria; Ruiz-Azuara, Lena (Frontiers in Molecular Biosciences, 2021)
The knowledge of the metabolic processes of designed metallodrugs for cancer treatment is an area that has been not profoundly studied. CasIIgly, which belongs to the Casiopeínas® family, is a copper (II) coordination compound that have shown a good biological activity against several cancer cells, low toxicity in normal cells and antineoplastic activity “in vivo” in murine and xenographted models. In this work we employed a triple negative highly metastatic breast carcinoma line (MDA-MB-231), which is one of the cancer types with a great mortality index, for its 1H-NMR-metabolomic analysis using cisplatin and CasIIgly, in order to know the effect of the metallodrugs in the metabolic profile of cell tumor line as a consequence of the treatment at different times. Our findings indicate that the cisplatin mainly acts towards phospholipid biosynthesis while the CasIIgly affects processes as carbohydrates and nucleotides metabolism. Also, we observed that CasIIgly treatment has an important and fast effect over MDA-MB-231 cells metabolism, which makes it a good alternative for the treatment in this type of cancer.